Seeing biological actions in 3D: An fMRI study. Issue 1 (29th October 2015) - Jastorff, Jan; Abdollahi, Rouhollah O.; Fasano, Fabrizio; Orban, Guy A.
Abstract: Precise kinematics or body configuration cannot be recovered from visual input without disparity information. Yet, no imaging study has investigated the role of disparity on action observation. Here, we investigated the interaction between disparity and the main cues of biological motion, kinematics and configuration, in two fMRI experiments. Stimuli were presented as point‐light figures, depicting complex action sequences lasting 21 s. We hypothesized that interactions could occur at any of the three levels of the action observation network, comprising occipitotemporal, parietal and premotor cortex, with premotor cortex being the most likely location. The main effects of kinematics and configuration confirmed that the biological motion sequences activated all three levels of the action observation network, validating our approach. The interaction between configuration and disparity activated only premotor cortex, whereas interactions between kinematics and disparity occurred at all levels of the action observation network but were strongest at the premotor level. Control experiments demonstrated that these interactions could not be accounted for by low level motion in depth, task effects, spatial attention, or eye movements, including vergence. These results underscore the role of premotor cortex in action observation, and in imitating others or responding to their actions. Hum Brain Mapp 37:203–219, 2016 . ©2015 The Authors Human Brain Mapping Published by Wiley Periodicals, Inc.